2018
DOI: 10.1002/pola.29169
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Transfer Suzuki–Miyaura Condensation Polymerization of Stilbene Monomer: Different Polymerization Behavior Depending on Halide and Aryl Group of ArPd(tBu3P)X Initiator

Abstract: We report Suzuki-Miyaura coupling polymerization of tetraalkoxy-substituted 4-bromostilbene-4 0 -boronic acid 1 with several t-Bu 3 P-ligated Pd initiators; this is the first example of catalyst-transfer condensation polymerization (CTCP) of a monomer containing a carbon-carbon double bond. When o-tolylPd( t Bu 3 P)Br was used as the initiator, the o-tolyl group was not introduced at the polymer end, but polymer with boronic acid at one end and bromine at the other was obtained. However, when we employed stilb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This catalyst system has been successful for the controlled polymerization of polythiophenes, polyfluorenes, and various polyphenylenes. 25,[36][37][38]43,45,[48][49][50][52][53][54][55][57][58][59] The success of t Bu 3 P-Pd has led to investigations to prepare more exotic polymers such as poly(3,6-phenanthrene), 54 poly(fluorene-altbenzothiadiazole), 58 and poly( pyridyl-alt-thiophene). 113 For poly(fluorene-alt-benzothiadiazole), Huck and coworkers were able to bring about controlled chain-growth polymerization of this large monomer system, though molecular weights were modest (3-7.3 kg mol −1 ).…”
Section: Ancillary Ligand Selectionmentioning
confidence: 99%
“…This catalyst system has been successful for the controlled polymerization of polythiophenes, polyfluorenes, and various polyphenylenes. 25,[36][37][38]43,45,[48][49][50][52][53][54][55][57][58][59] The success of t Bu 3 P-Pd has led to investigations to prepare more exotic polymers such as poly(3,6-phenanthrene), 54 poly(fluorene-altbenzothiadiazole), 58 and poly( pyridyl-alt-thiophene). 113 For poly(fluorene-alt-benzothiadiazole), Huck and coworkers were able to bring about controlled chain-growth polymerization of this large monomer system, though molecular weights were modest (3-7.3 kg mol −1 ).…”
Section: Ancillary Ligand Selectionmentioning
confidence: 99%
“…Most high-performing donor–acceptor polymers are synthesized in a step-growth manner from two difunctionalized monomers (e.g., a dihalide and a distannane) using tetrakis­(triphenyl)­phosphine palladium (Pd­(PPh 3 ) 4 ). , Similar to the infancy of palladium-catalyzed small-molecule cross-coupling, , Pd­(PPh 3 ) 4 is the workhorse precatalyst for conjugated polymers and is often used despite forming undesired (e.g., homocoupled) byproducts. In Pd-catalyzed small-molecule cross-coupling, however, significant developments in catalyst design have now enabled electron-deficient and -rich substrates with unprotected functional groups to be synthesized with few side products. While hundreds of ancillary ligands have been screened and optimized for these small-molecule cross-coupling reactions, comparatively few have been explored for synthesizing conjugated polymers, leaving a vast range of potential Pd precatalysts for CTP (Chart ) ,,, These ligands have been specifically optimized for Pd and, as such, will likely be more successful on Pd than on Ni for CTP . Herein, we highlight select examples of catalysts used in small-molecule cross-couplings as inspiration for expanding CTP.…”
Section: Why Palladium?mentioning
confidence: 99%
“…Yokozawa and co-workers also found that Pd outperforms Ni when synthesizing poly­( p -phenylene vinylene) (PPV). They hypothesized that the Ni became “trapped” on the CC bond in a π-complex that was too stable. , Similarly, Koeckelberghs and co-workers showed that a tBu 3 P-ligated Pd precatalyst could polymerize thieno­[3,2- b ]­thiophene where Ni precatalysts with a variety of ancillary ligands (e.g., dppp, dppe, depe, IPr) failed . This failed polymerization was attributed to Ni trapping via a strong π-complex with the thienothiophene dimer formed in the initial reductive elimination.…”
Section: Why Palladium?mentioning
confidence: 99%